2018
DOI: 10.3846/btp.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Group-Tacit Knowledge and Organisational Effectiveness: Analysis of Effects Using a Mixed Method Approach

Abstract: and being under the tutelage of experts. This implies that group-tacit knowledge reflects in the experiences shared on the job and the expertise that arises by reason of learning subtle skills and know-hows that are not common to most members of a profession and, indeed, the organisation.According to Li, Chang, Chen and Jiang (2010) grouptacit knowledge has the advantage of enhancing the effectiveness of organisational members' ability to forecast events relating to their operations. This is because, leveragin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The results from these various analysis, largely explain the reasons for the growing level of poverty and shortage in food supply in SSA countries. Generally, agricultural labour is considered to be pivotal to the success of any production unit, both at the micro- and macro-level of analysis (Nolte and Ostermeier, 2017; Ibidunni et al , 2018). It therefore, holds that for agricultural production to yield more significant outcomes, based on this present study, government in the SSA region must pay attention to efficient and effective utilisation of labour employment in the agricultural sector of the respective economies.…”
Section: Discussionmentioning
confidence: 99%
“…The results from these various analysis, largely explain the reasons for the growing level of poverty and shortage in food supply in SSA countries. Generally, agricultural labour is considered to be pivotal to the success of any production unit, both at the micro- and macro-level of analysis (Nolte and Ostermeier, 2017; Ibidunni et al , 2018). It therefore, holds that for agricultural production to yield more significant outcomes, based on this present study, government in the SSA region must pay attention to efficient and effective utilisation of labour employment in the agricultural sector of the respective economies.…”
Section: Discussionmentioning
confidence: 99%
“…Using a qualitative means of data gathering and thematic analysis, the study revealed that organizational knowledge dimensions such as individual-tacit, individual-explicit, group-tacit and group-explicit knowledge are essential to achieving organizational objectives and higher levels of performance. The possible reason for these findings could be that the firm largely promotes a collective use of knowledge more, or rather, than individualism (Ibidunni et al, 2018c). This is such that, in using knowledge to resolve customer complaints, especially those that are beyond the coverage of the firm's online knowledge base, employees would rather seek collective solutions than attempt to individually seek out a means to the customers' queries (Fei et al, 2009;Huang, 2014;Ibidunni et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Group-tacit knowledge is the mutually upheld organizational image, norms and cultural patterns that direct how work is done (Fei et al, 2009). It is significant for sustaining organizational competitiveness and ensuring the sustainability of such positions by combining the tacit reasoning of organizational members in work tasks (Erden et al, 2008;Swart and Pye, 2003;Ibidunni et al, 2018c).…”
Section: Operationalizing Organizational Knowledgementioning
confidence: 99%
“…However, and very surprisingly, work experience did not show any direct relationship with customer satisfaction. Therefore, employees' position in the organisation and its influence on customer satisfaction will result from the direct relationships that customer care representative of the telecommunication organisations have with their customers (Ibidunni, Olokundun, Motilewa, Atolagbe, & Osibanjo, ; Tsoukas & Vladimirou, ). The direct effect of firm size on customer satisfaction and organisational effectiveness was also statistically significant.…”
Section: Discussionmentioning
confidence: 99%